Adaptation, Academic Performance and Support: Students with and without Disabilities and Future Considerations for Counselling Psychology - Panagiotis Parpottas; Yianna Christofi; Ioanna Ioannou (Behavioral Sciences, 2023)
The transition to university is a process that presents young adults with several challenges in adaptation, especially students with disabilities. The current study investigated the differences in adaptation and academic performance between students with and without disabilities and further examined these differences among students with disabilities. Additionally, we explored the role of academic support for students with disabilities’ adaptation and academic performance, as well as their perceptions of a proposed specialised package of counselling psychology interventions. The sample consisted of 127 students with disabilities and 127 without disabilities, aged 18–24 years. Results revealed that students with disabilities reported a lower GPA and adaptation than students without disabilities. Additionally, differences among students with disabilities were observed only in terms of GPA, according to their disability type, existence of comorbidity and type of exam accommodations. Interestingly, no differences were found in GPA or adaptation between students with disabilities who utilised psychological therapy and those who did not. Finally, adaptation scores, but not GPA, were higher for students with disabilities who were positive in receiving a specialised package of counselling psychology interventions. The findings are discussed in relation to the existing literature and future considerations of counselling psychology’s role in support of students with disabilities.